Self-reported injury history and lower limb function as risk factors for injuries in female youth soccer - Steffen, K.; Myklebust, G.; Andersen, T. E.; Holme, I.; Bahr, R. (The American Journal of Sports Medicine, 2008)
Background: Identifying and understanding injury risk factors are necessary to develop and target measures to prevent injuries. Because youth teams rarely have health care professionals working directly with the team, identifying players at increased risk through elaborate clinical tests is not feasible. Questionnaires may be a possible alternative as screening instruments.